2021
DOI: 10.1097/wno.0000000000001390
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Outcomes of Acquired Pediatric Sixth Nerve Palsies

Abstract: Background:Acquired sixth nerve (CN6) palsies in children may be benign or associated with an underlying neurologic condition. In children who presented with isolated (no associated neurologic or ophthalmic symptoms or signs) CN6 palsies, the rate of newly diagnosed neurologic disorders (such as tumors) is unclear. Moreover, the factors associated with spontaneous resolution and amblyopia in children with acquired CN6 palsies are unknown.Methods:We retrospectively reviewed the charts of all children younger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Despite the commonly held belief that acquired esotropia is a benign condition, recent research has revealed the potential for serious neurological pathologies even in patients with normal neurological examination. 5,[24][25][26][27] In this study, 113 cases (63.8%) displayed normal neurological findings, while 26 cases (14.7%) were diagnosed with lifethreatening conditions such as tumors, inflammation, and vascular lesions. Additionally, degeneration and other pathologies were observed in 38 cases (21.5%).…”
Section: Discussionmentioning
confidence: 67%
“…Despite the commonly held belief that acquired esotropia is a benign condition, recent research has revealed the potential for serious neurological pathologies even in patients with normal neurological examination. 5,[24][25][26][27] In this study, 113 cases (63.8%) displayed normal neurological findings, while 26 cases (14.7%) were diagnosed with lifethreatening conditions such as tumors, inflammation, and vascular lesions. Additionally, degeneration and other pathologies were observed in 38 cases (21.5%).…”
Section: Discussionmentioning
confidence: 67%
“…Based on these results, the etiology of the abducens nerve palsy of the patient was considered due to infectious disease. In children, abducens nerve palsy is rarely caused after an upper respiratory tract infection known as "benign isolated abducens nerve palsy", and it has been suggested to be related to Mycoplasma or other viral infections [8,9]. In adults, we only found a case of a 52-year-old man who developed abducens nerve palsy due to a Mycoplasma infection, showing choreoathetoid movements and an acute psychosis, suggesting he had suffered from encephalitis and not exclusively abducens nerve palsy [10].…”
Section: Discussionmentioning
confidence: 99%
“…1 Lesions might be isolated 2,3 or with additional cranial nerve involvement. 4 Generally, frequent causes of children's abducens nerve palsy are often associated with postviral or postvaccination, idiopathic, trauma, elevated intracranial pressure, neoplasm, or viral infections; [5][6][7] while in adults are microvascular diseases, vasculopathies, tumors, and inflammatory conditions. 8,9 Ten years cohort study showed the etiologies of old population were presumed to be vascular (56.6%), idiopathic (27.2%), neoplastic (5.6%), and traumatic (4.9%).…”
Section: Introductionmentioning
confidence: 99%